ANALISIS VIRTUAL REALITY PADA GAME VR LOUNGE ROOM: CREED RISE TO GLORY - Revlon Ramadhanti; Dimas Harianto, Rahmat Afdal, Bayu Rahmat Rifdian, Aryani Carissa Puteri, Arifah Kurnia Putri, Isna (Jurnal Komunikasi, 2024)
Creed: Rise to Glory" is a game that utilizes Virtual Reality (VR) technology to create an immersive experience in the world of boxing. This game allows players to experience the sensation of being a boxer through the use of a VR headset and accurate motion tracking technology. This research analyzes various aspects of the use of VR in "Creed: Rise to Glory," including immersion and realism, physical interactions, psychological eflects, applications in health and rehabilitation, as well as challenges and potential for future development. The research results show that the VR technology in this game successfully creates a high level of immersion and deep realism, with the player's body movements accurately reflected in the game. The use of VR also aflects the player's emotional and cognitive responses, increasing adrenaline and focus. In addition, the potential applications of VR in physical therapy and rehabilitation are very promising, opening up new opportunities in the health sector. However, VR game development faces various technical and economic challenges that need to be overcome to create engaging and eflective content. Nonetheless, the success of “Creed: Rise to Glory” shows the huge potential of VR technology in the gaming industry, with opportunities for continued innovation in game design and technology. This game also has significant social and educational potential, especially in multiplayer interactions and educational simulations. Overall, "Creed: Rise to Glory" not only oflers entertainment, but also contributes to the development of VR technology, opening up new opportunities in various fields and showing a bright future for the VR gaming industry